Pengaruh Pemberian Insentif terhadap Motivasi Kerja Pegawai pada Kantor Lembaga Penjaminan Mutu Pendidikan (LPMP) Bandar Lampung - Aprilianto Amir; Riswati (Business Perspective Journal, 2021)
Human resources have a very important role in an agency, for that in order for the agency to achieve goals as expected, high employee motivation is needed. Generating a high employee motivation is not easy to implement. Therefore, employees should be given appropriate incentives so that the desired employee motivation can be achieved. The provision of incentives can be done by providing annual bonuses, employee welfare, and promotions. As for the main problem with this research is "does the provision of incentives affect the work motivation of employees at the Office of the Education Quality Assurance Institute (LPMP) Bandar Lampung?" In line with the main problem, the authors propose the hypothesis "There is a positive influence between the provision of incentives on employee motivation at the Office of the Education Quality Assurance Institution (LPMP) Bandar Lampung". In the research that the author did, the research variable was the provision of incentives as the independent variable (X) while employee motivation as the dependent variable (Y). Furthermore, the proposed sample is 26 employees which is 25% of the total population, namely 105 employees. The type of research in this writing is qualitative and quantitative research with the method used is to collect data by means of surveys or field research. While the data collection techniques by means of observation, documentation, interviews and questionnaires. Then to test the hypothesis using qualitative and quantitative analysis which is the type of this writing, with statistical formulas. Quantitative analysis using the product moment formula and obtained: rxy product moment = 0.714. Confused with the level of evenness of the 2 variables being at a high level of closeness, it means that the incentive distribution has a very high relationship with employee performance. To find out the effect of giving incentives on employees' work motivation, using a determinant coefficient with a result of 51%, while other factors 49% were not examined including leadership style, office layout, atmosphere (work climate) of employees. Keywords: incentives, work motivation, Education Quality Assurance Institute